2013
DOI: 10.1097/nen.0b013e3182a74372
|View full text |Cite
|
Sign up to set email alerts
|

A Derivative of the Brain Metabolite Lanthionine Ketimine Improves Cognition and Diminishes Pathology in the 3×Tg-AD Mouse Model of Alzheimer Disease

Abstract: Lanthionine ketimine ([LK] 3,4-dihydro-2H-1,4-thiazine-3,5-dicarboxylic acid) is the archetype for a family of naturally occurring brain sulfur amino acid metabolites, the physiologic function of which is unknown. Lanthionine ketimine and its synthetic derivatives have recently demonstrated neurotrophic, neuroprotective, and antineuroinflammatory properties in vitro through a proposed mechanism involving the microtubule-associated protein collapsin response mediator protein 2. Therefore, studies were undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 66 publications
0
51
0
Order By: Relevance
“…Treatment with LKE at pharmacologically-relevant (Hensley et al, 2013), low µM concentrations increased autophagic lipidation of LC3-I to LC3-II by 2 to 3-fold in SH-SY5Y cells with similar effects observed in RG2 glioma cells (Figs. 1–2).…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…Treatment with LKE at pharmacologically-relevant (Hensley et al, 2013), low µM concentrations increased autophagic lipidation of LC3-I to LC3-II by 2 to 3-fold in SH-SY5Y cells with similar effects observed in RG2 glioma cells (Figs. 1–2).…”
Section: Resultsmentioning
confidence: 66%
“…At 24h in RG2 cells, LKE affected the ULK1 system with EC50 of approximately 50 nM (Fig. 3) which is 10–100 fold lower than pharmacologically achievable brain concentrations (Hensley et al, 2013) and near the reported brain physiological concentration of LK (Fontana et al, 1997). This is also within the concentration range at which LKE potentiates neurite outgrowth in NSC-34 motor neuron-like cells and primary dorsal root ganglial neurons (Hensley et al 2011; Hensley and Denton 2015).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations